Cardioselective peripheral noradrenergic deficiency in Lewy body synucleinopathies. Issue 12 (20th November 2020) - Lamotte, Guillaume; Holmes, Courtney; Sullivan, Patricia; Lenka, Abhishek; Goldstein, David S.
Abstract: Objective: Lewy body (LB) synucleinopathies such as Parkinson's disease (PD) entail profound cardiac norepinephrine deficiency. The status of sympathetic noradrenergic innervation at other extracranial sites has been unclear. Although in vivo neuroimaging studies have indicated a cardioselective noradrenergic lesion, no previous study has surveyed peripheral organs for norepinephrine contents in LB diseases. We reviewed 18 F‐dopamine ( 18 F‐DA) positron emission tomographic images and postmortem neurochemical data across several body organs of controls and patients with the LB synucleinopathies PD and pure autonomic failure (PAF) and the non‐LB synucleinopathy multiple system atrophy (MSA). Methods: 18 F‐DA–derived radioactivity in the heart, liver, spleen, pancreas, stomach, kidneys, thyroid, and submandibular glands were analyzed from 145 patients with LB synucleinopathies (112 PD, 33 PAF), 74 controls, and 85 MSA patients. In largely separate cohorts, postmortem tissue norepinephrine data were reviewed for heart, liver, spleen, pancreas, kidney, thyroid, submandibular gland, and sympathetic ganglion tissue from 38 PD, 2 PAF, and 5 MSA patients and 35 controls. Results: Interventricular septal 18 F‐DA–derived radioactivity was decreased in the LB synucleinopathy group compared to the control and MSA groups (P < 0.0001 each). The LB and non‐LB groups did not differ in liver, spleen, pancreas, stomach, or kidney 18 F‐DA–derived radioactivity. The LB synucleinopathy group had markedly decreased apical myocardial norepinephrine, but normal tissue norepinephrine in other organs. The MSA group had normal tissue norepinephrine in all examined organs. Interpretation: By in vivo sympathetic neuroimaging and postmortem neurochemistry peripheral noradrenergic deficiency in LB synucleinopathies is cardioselective. MSA does not involve peripheral noradrenergic deficiency.